In vitro determination of ciprofloxacin resistance in Pseudomonas aeruginosa biofilms and hospital planktonic populations - Florián, Christian (2006)
Objective: To assess in vitro sensitivity / resistance of biofilms and planktonic populations of Pseudomonas aeruginosa from a hospital environment to ciprofloxacin and to compare them against the results of standard susceptibility test obtained. Design: Microbiological study. Setting: Molecular Microbiology Laboratory, Faculty of Biological Sciences, UNMSM. Biologic material: Pseudomonas aeruginosa strains. Interventions: Resistant and susceptible strains obtained form Hospital del Niño were tested for minimum inhibitory concentration (MIC); then biofilms were formed on filtration membranes, and planktonic cultures in broth were tested with different ciprofloxacin concentrations, with plate count at 40 minutes intervals and 24 hours after exposure. Main outcome measures: In vitro susceptibility / resistance of hospital origin Pseudomonas aeruginosa biofilms and planktonic populations. Results: Sensitive strains increase their resistance more than 200 times under biofilm growth; no significant difference was found with resistant strains and both start to decrease their population at about 128 ìg/mL drug concentration. Conclusions: The same strain, as in case of Pseudomona aeruginosa, has a different response to ciprofloxacin, according to its growth. A MIC biofilm test of recurrent and chronic infections etiological agents is recommended.